Application of an independent parallel reactions model on the annealing kinetics to irradiated graphite waste - Lasithiotakis, M; Marsden, B; Marrow, J; Willets, A (2008)
The first generation of UK research and production reactors were graphite moderated and operated at low temperatures, below 150 °C. The graphite in these reactors now contains a significant amount of stored (Wigner) energy that may be relatively easily released by heating the graphite above the irradiation temperature. This exothermic behaviour has lead to a number of decommissioning issues which are related to characterization of graphite samples, long term "safe-storage", reactor core dismantling, graphite waste packaging and the final disposal of this irradiated graphite waste. The release of stored energy can be modelled using kinetic models linked to classical kinetic analysis theory. These models rely on Differential Scanning Calorimeter (DSC) data obtained either from graphite samples irradiated in material test reactors or data obtained from small samples trepanned from the reactors themselves. Data from these experiments can be used to derive activation energies and characteristic functions used in kinetic models for application to practical situations using suitable modelling techniques. In this paper the classical theory of kinetic analysis is used as the basis for models applied to the study of stored energy release in irradiated graphite components. The use of an independent parallel reactions model is proposed and several possible kinetic model scenarios are tested. © 2008 Elsevier B.V. All rights reserved.